Developments since the Fourth WTO Ministerial Conference : agriculture (International Centre for Trade and Sustainable Development GenevaCH, 2003)
Provides a background to the topic and lists mandated deadlines. Focuses on the current state of play and highlights the many outstanding issues and questions regarding market access, export competition and domestic support. Looks also at special and differential treatment. Identifies implementation issues.
Keywords: TRADE NEGOTIATIONS